A COMPARATIVE STUDY TO ASSESS THE KNOWLEDGE AND ATTITUDE BETWEEN POSTGRADUATE NURSING STUDENTS AND LLB STUDENTS REGARDING EUTHANASIA IN SELECTED COLLEGES OF UDUPI DISTRICT - Verghese, Ashley Elizabeth; Mathew, Prince; Salins, Ronald; Mathew, Sminu; Kuriakose, Basil; Shobha (Journal of Health and Allied Sciences NU, 2014)
The concept of euthanasia is based on the philosophy of humanism and compassion. It recognizes the autonomy of an individual, freedom of choice to live or die with dignity. It is a very sensitive issue that polarized the world. Euthanasia is one of the most perplexing issues which the world faces today.In this study, the knowledge of postgraduate nursing students and LLB students was assessed by using structured knowledge questionnaire and attitude by attitude scale. The findings of the study revealed that out of 40 postgraduate nursing students, 57.5% were Christians, 35% were Hindus and 7.5% were belonged to other religious groups. Among the LLB students 85% were Hindus, 12.5% were Muslims and 2.5% were Christians. Among the postgraduate nursing students, 80% were females and among LLB students, 60% were females. The result also showed that, 62.5% of the nursing and LLB students had good knowledge and 65% of the nursing students and 57.5% of the LLB students were favouring euthanasia respectively. There was no significant difference between knowledge of nursing students and LLB students.
Keywords: euthanasia; postgraduate nursing students; LLB students